Perspectives of world-class endurance coaches on the evolution of athlete training and performance - Sandbakk, Ø.; Herzog, S.; McGawley, K.; Pyne, D. B.; Talsnes, R. K.; Millet, G. P.; Solli, G. S.; Seiler, S.; Laursen, P. B.; Haugen, T.; Tønnessen, E.; Wilber, R.; et al. (International Journal of Sports Physiology and Performance, 2025)
Purpose: To provide insights into the key practices driving the evolution of endurance training and performance. Methods: A total of 78 world-class coaches (73 men, 5 women), representing 14 endurance sports, and 18 nations, participated in a digital survey comprising open-ended questions about recent trends and projected future developments. Results: Qualitative thematic analysis revealed 8 key drivers of change: (1) individualized and sport-specific training strategies, (2) precision in training execution, (3) load-management procedures, (4) strategic use of environmental stressors, (5) optimized nutrition, (6) holistic recovery practices, (7) health and injury prevention, and (8) equipment and technology-driven innovation. To provide a clearer conceptual framework, these themes were grouped into 3 overarching categories: training methodologies (themes 1-4), recovery and health management (themes 5-7), and technological innovation (theme 8). Conclusions: World-class endurance coaches describe a continuing shift toward more individualized training strategies, characterized by detailed sport-specific considerations, training plans aligned with physiological profiles, greater precision in training execution, refined load management, and strategic use of environmental stressors. In this context, advanced monitoring technologies are viewed as essential for optimizing training adaptations while minimizing the risk of maladaptation and injury. Coaches also emphasized the importance of enhanced health and recovery strategies to support training adaptations, including sleep quality, stress management, life balance, and targeted nutritional interventions, particularly carbohydrate availability. Finally, the rapid development of new equipment and technologies is transforming training and coaching practices, thereby contributing to improved endurance performance.